CAR-T Cells in the Treatment of Urologic Neoplasms: Present and Future - Zhang, Zhengchao; Li, Dong; Yun, Heng; Liu, Wei; Chai, Keqiang; Tong, Jie; Zeng, Tongwei; Gao, Zhenghua; Xie, Yongqiang (Frontiers in Oncology, 2022)
In recent years, with the breakthrough of CAR-T cells in the treatment of hematological tumors, they are increasingly being used to treat solid tumors, including urologic neoplasms. There are many relatively specific targets for urologic neoplasms, especially prostate cancer. Besides, urologic neoplasms tend to progress more slowly than tumors in other organs of the body, providing ample time for CAR-T cell application. Therefore, CAR-T cells technology has inherent advantages in urologic neoplasms. CAR-T cells in the treatment of urologic neoplasms have been extensively studied and preliminary achievements have been made. However, no breakthrough has been made due to the problems of targeting extra-tumor cytotoxicity and poor anti-tumor activity. we systematacially summarized the research actuality of CAR-T cells in urologic neoplasms, discussed the potential value and difficulties of the research. The application of CAR-T cells in the treatment of urologic neoplasms requires improvement of function through screening for better targets, modification of CAR structures, or in combination with other antitumor approaches.